Novel method to improve engine exhaust energy extraction with active control turbocharger. (February 2014) - Rajoo, Srithar; Pesiridis, Apostolos; Martinez-Botas, Ricardo
A mixed-flow turbine with pivoting nozzle vanes was designed and tested to actively adapt to the pulsating exhaust flow (called the active control turbocharger). The turbine was tested at an equivalent speed of 48, 000 r/min with inlet flow pulsation of 40 and 60 Hz, which corresponds to a four-stroke diesel engine speed of 1600 and 2400 r/min, respectively. The nozzle vane operating schedules for each pulse period are evaluated experimentally in two general modes: natural opening and closing of the vanes due to the pulsating flow and the forced sinusoidal oscillation of the vanes to match the incoming pulsating flow. The turbine energy extraction as well as efficiency is compared for the two modes to formulate its effectiveness. In addition, a one-dimensional commercial code was implemented, matching an active control turbocharger to an engine with equivalent characteristics to the one simulated in the laboratory. The results obtained represented an improvement over the experimental data with the engine power increasing by between 3.58% and 7.76% between 800 and 1400 r/min; the actual turbocharger power recovery required to achieve this increase in engine power was far higher and typically exceeded 20% throughout the lower half of the engine speed range while remaining higher than 10% for most of the rest. The aim of this article is to demonstrate the potential of active control turbocharger in relation to current turbocharging practice. It has shown strong potentials to improve engine performance in parts of the operational envelope, which need to be further harnessed for real-life applications.